2013
DOI: 10.1016/j.actamat.2013.08.001
|View full text |Cite
|
Sign up to set email alerts
|

The origin of anomalous eutectic structures in undercooled Ag–Cu alloy

Abstract: A melt encasement (fluxing) method has been used to undercool Ag-Cu alloy at its eutectic composition. The recalescence of the undercooled alloy has been filmed at high frame rate. For undercoolings < 60 K a microstructure consisting of mixed anomalous and lamellar eutectic is observed. Analysis of eutectic spacing in the lamellar eutectic reveals little dependence upon the undercooling of the bulk melt and is consistent with growth at an undercooling of 1.5 K.Depending upon undercooling, the progress of the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
22
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(30 citation statements)
references
References 33 publications
6
22
0
Order By: Relevance
“…This result agrees with the findings in previous works, where it was observed that the volume fraction of the anomalous eutectic phase increases when undercooling of the eutectic reaction increases in the binary Ni-B system [23] and in other eutectic systems in binary alloys, such as Ag-Cu [29,30] and Ni-P [30]. An important feature of the R1 s -R2 s reaction sequence observed at high eutectic undercooling is that R2 s presents a high recalescence: 15 • C and 60 • C in the DSC and CCT experiments, respectively.…”
Section: Coolingsupporting
confidence: 83%
“…This result agrees with the findings in previous works, where it was observed that the volume fraction of the anomalous eutectic phase increases when undercooling of the eutectic reaction increases in the binary Ni-B system [23] and in other eutectic systems in binary alloys, such as Ag-Cu [29,30] and Ni-P [30]. An important feature of the R1 s -R2 s reaction sequence observed at high eutectic undercooling is that R2 s presents a high recalescence: 15 • C and 60 • C in the DSC and CCT experiments, respectively.…”
Section: Coolingsupporting
confidence: 83%
“…These have the same phase constitution, 1 -Ni 3 Si and Ni 25 Si 9 , but are morphologically distinct with (I) being a regular lamellar structure and (II) being a much more disordered eutectic structure. In fact it is clear that the structure II has the features of an anomalous eutectic, a structure that is widely observed [36,37] in the solidification of eutectic alloys from their undercooled parent melt, wherein the distinct lamellar morphology of a regular eutectic cannot be observed. Many studies [36,37] have indicated that the fraction of anomalous eutectic structure increases with increasing undercooling.…”
Section: Discussionmentioning
confidence: 99%
“…In fact it is clear that the structure II has the features of an anomalous eutectic, a structure that is widely observed [36,37] in the solidification of eutectic alloys from their undercooled parent melt, wherein the distinct lamellar morphology of a regular eutectic cannot be observed. Many studies [36,37] have indicated that the fraction of anomalous eutectic structure increases with increasing undercooling. The structure II can be observed in all ranges of type B droplet, while the fraction of the regular structure (I) presents a decreasing trend with decreasing particle size and has almost disappeared in all of the 75-106 m droplets.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the increase of undercooling, the solidification rate increases and the solidification structures can be composed of a mixture of lamellar eutectics and anomalous eutectics or full anomalous eutectics [4][5][6][7][8]. Furthermore, the rapidly solidified alloys can have a series of good properties, such as high strength and toughness, high temperature creep resistance, electromagnetism and corrosion resistance, etc., because the properties of the as-solidified materials are determined by the conditions under which the liquid solidifies.…”
Section: Introductionmentioning
confidence: 99%